A New Forward-Flyback Based Single Switch Single Stage PFC Converter - Bodur, Hac; Kaya, Koray Y.; Akboy, Erdem; Aksoy, Ismail (IEEE, 2015)
In this study, a new forward-flyback based single switch single stage power factor correction (PFC) converter is presented. This circuit provides PFC, direct power transfer (DPT) and tight output voltage regulation with only single switch and controller. The switch turns on with zero current switching (ZCS) but turns off with hard switching. In this study a detailed steady state analysis of the new converter is presented and the theoretical analysis is verified for 100 kHz and 100 W simulation results with PSIM programme.
Keywords: Energy & Fuels; Engineering